Transitions in nirS-type denitrifier diversity, community composition, and biogeochemical activity along the Chesapeake Bay estuary - Francis, Christopher A.; O'Mullan, Gregory D.; Cornwell, Jeffrey C.; Ward, Bess B. (Frontiers in Microbiology, 2013)
Chesapeake Bay, the largest estuary in North America, can be characterized as having steep and opposing gradients in salinity and dissolved inorganic nitrogen along the main axis of the Bay. In this study, the diversity of nirS gene fragments (encoding cytochrome cd1-type nitrite reductase), physical/chemical parameters, and benthic N2-fluxes were analyzed in order to determine how denitrifier communities and biogeochemical activity vary along the estuary salinity gradient. The nirS gene fragments were PCR-amplified, cloned, and sequenced from sediment cores collected at five stations. Sequence analysis of 96 to 123 nirS clones from each station revealed extensive overall diversity in this estuary, as well as distinct spatial structure in the nirS sequence distributions. Both nirS-based richness and community composition varied among stations, with the most dramatic shifts occurring between low-salinity (oligohaline) and moderate-salinity (mesohaline) sites. For four samples collected in April, the nirS-based richness, nitrate concentrations, and N2-fluxes all decreased in parallel along the salinity gradient from the oligohaline northernmost station to the highest salinity (polyhaline) station near the mouth of the Bay. The vast majority of the 550 nirS sequences were distinct from cultivated denitrifiers, although many were closely related to environmental clones from other coastal and estuarine systems. Interestingly, 8 of the 172 OTUs identified accounted for 42% of the total nirS clones, implying the presence of a few dominant and many rare genotypes, which were distributed in a non-random manner along the salinity gradient of Chesapeake Bay. These data, comprising the largest dataset to investigate nirS clone sequence diversity from an estuarine environment, also provided information that was required for the development of nirS microarrays to investigate the interaction of microbial diversity, environmental gradients, and biogeochemical activity.